Effectiveness of implementing clinical practice guidelines to promote advanced care planning for cancer patients receiving palliative care: an implementation research study - K, Moonthee; P, Soivong; W, Udomkhamsuk (Biomedical Sciences and Clinical Medicine, 2021)
Objectives To examine the effectiveness of implementing clinical practice guidelines (CPGs) for the promotion of advanced care planning for cancer patients receiving palliative care. Methods This research was conducted to implement clinical practice guidelines based on the framework proposed by the National Health and Medical Research Council of Australia, including preparation and dissemination of CPG, training of adopting personal, establishment of collaboration and continuous monitoring strategies, and evaluation of results. Participants consisted of two groups: group 1 included 52 cancer patients receiving palliative care prior to CPG implementation and 33 cancer patients receiving palliative care during the CPG implementation process. Group 2 included 14 health care personal who utilized CPGs. The data were analyzed using descriptive statistics. Results The desires, expectations, needs, and choices regarding treatment had been expressed by only 11.54% of participants prior to CPGs implementation, while during the implementation process 81.82% indicated their feelings regarding these domains. Before implementation, 23.08% of the participants mentioned the need for a care plan related to relieving unpleasant symptoms, while during the CPG implementation, 90.91% indicated a need for such a plan. Most healthcare personnel (85.71%) expressed a high level of overall satisfaction with the utilization of CPGs. Conclusions Implementing CPG to promote advanced care planning for cancer patients receiving palliative care can promote advanced care planning be effective. The health care providers who followed these guidelines expressed a high level of satisfaction with CPG development and are anticipated to have a similarly high level of satisfaction with CPG implementation. Implementation of CPG for the care of cancer patients should be proposed to hospital administrations.